Determinants Of Sustainability Report Disclosure in Indonesia’s Energy Sector (E-Jurnal Akuntansi, 2026)
This study is motivated by the disparity in the level of disclosure in Sustainability Reports based on GRI standards, as well as the inconsistencies in the findings of previous studies. This study aims to analyze the influence of profitability, firm size, leverage, institutional ownership, and managerial ownership on sustainability report disclosure among energy sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. This study uses secondary data with a purposive sampling technique, covering 28 companies with a total of 84 observations, and analyzed using multiple linear regression. The results of the study indicate that profitability, firm size, leverage, and institutional ownership have a significant effect on sustainability report disclosure, whereas managerial ownership does not have a significant effect. These findings indicate that external pressures are more dominant in driving corporate transparency and have implications for stakeholders in evaluating sustainability accountability.
Keywords: Disclosure of Sustainability Reports; Profitability; Firm Size; Leverage; Institusional Ownership; Managerial Ownership